Karakteristik Pemilihan Moda Transportasi Rute Nunukan-Tarakan - Daud Nawir; Achmad Zultan Mansur (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2018)
The research aims to determine the characteristics and satisfaction models of speed boat, ferry and plane transportation routes for the Nunukan-Tarakan aircraft. Survey data using descriptive methods and multiple linear regression methods using SPSS v16. From the survey results, it is found that the characteristics of ferry transportation agents aged 17-27, male and female sex, high school education/equivalent, type of work are students, earning Rp2,500,000, and recreational trips. The characteristics of speed boat transportation are 17-27, male, last education is high school/equivalent, work is student, income is IDR 2,500,000-3,000,000, and recreational trips. The characteristics of airplane transportation modes are the majority of the age of 28-38 years, sex is male, last education is undergraduate, civil servant employment income IDR 3,000,000-5,000,000, and work/business travel destination. Equation model satisfaction for each mode of transportation, for the Y Ferry model = 0.493 + 0.726X1 - 0.017X2 - 0.163X3, Y Speed boat = 0.128 + 0.897X1 - 1.279X2 - 0.114X3, and Y Aircraft = 0.253 + 0.400X1 + 0.195X2 - 0.250X3.